Batman v Superman : [videorecording (DVD)] dawn of justice - Kane, Bob; Finger, Bill, 1914-1974; Siegel, Jerry, 1914-1996; Shuster, Joe, 1914-1992 (Warner Home Video, 2016)
Fearing the actions of Superman are being left unchecked, Batman takes him on, while the world wrestles with what kind of a hero it really needs. With Batman and Superman fighting each other, a new threat, Doomsday, is created by Lex Luthor. It's up to Superman and Batman to set aside their differences, along with Wonder Woman, to stop Lex Luthor and Doomsday from destroying Metropolis.